Influence of compositions ABRO GT-409 and POLYTRONMТС in transmission oil on tribological contact in material systems "CuCrNiZrTi - KCh50", "CuCrNiZrTi – 40X" - Kubich, V.I.; Cherneta, O.G.; Yurov, V.M. (Journal of Physics: Conference Series, 2022)
The work carried out definitive tribotechnical tests of the systems of materials "CuCrNiZrTi - 85W90 - 40X", "CuCrNiZrTi - 85W90 - KCh50" to assess the nature of the manifestation of the effect of additive compositions (AC) ABRO GT-409 and POLYTRONTMС on adaptability to loading and lubrication modes parameters of adhesion properties when modeling shear on small samples. It was found that at the stage of running-in, the systems of materials operate stably with clearly pronounced tendencies to reduce the sliding resistance to a certain minimum, followed by its increase due to the influence of the AC components. ACs do not determine the effect of reducing the wear intensity in the investigated range of contact pressures, and a decrease in friction is caused by a decrease in shear resistance in the zones of significant effect on the decrease in the parameters of adhesion properties is exerted by the POLYTRONМТС 10% AC components, which cause the formation of secondary lubricant formations with denser structures at the interface of adhesion with metal surfaces and reduced resistance to movement within the formed cohesive bonds between them.